The Memorizing, Marking and Scanning (MMS) Method for Qur’an Memorization in An-Nur 2 Al-Murtadlo: A Grounded Theory Study - Ahmad Sulaiman; Fazlur Rahman Rahawarin; Jaynal Ilmi; Sonyalita Bintang Rivanda; Fantika Febri Puspitasari (Amorti: Jurnal Studi Islam Interdisipliner, 2026)
This study was motivated by the rapid growth of Qur'an memorization (tahfidz) institutions in Indonesia, creating the need for structured cognitive strategies to overcome memory load and improve the retention of mutashabihat (similar) verses. The study explored the cognitive processes underlying the Memorizing, Marking, and Scanning (MMS) method developed at An-Nur 2 Islamic Boarding School, Bululawang. Using a qualitative approach with a Constructivist Grounded Theory design, data were collected through in-depth interviews, participant observation, and Focus Group Discussions involving seven participants, including the method's initiator, facilitators, and students. The findings indicate that MMS is more than a conventional memorization technique; it is a cognitive learning system integrating Information Processing Theory and Dual Coding Theory. The Memorizing stage strengthens verbal-auditory memory through repetition, Marking serves as a metacognitive monitoring process to identify and correct memory gaps, and Scanning reinforces retention through visual-spatial memory cues. The effectiveness of the method is supported by students' self-regulation in managing limited study time and facilitators' flexibility in accommodating different learning styles. In conclusion, MMS represents a holistic and adaptive cognitive intervention that enhances the long-term retention of Qur'an memorization. The findings provide a new theoretical framework for improving Qur'an memorization learning management in contemporary educational settings.